Applying grounded theory to data collected through participatory research on African Independent Churches" liturgical rituals: A comparative study - Müller, Bethel A. (HTS teologiese studies, 2011)
This article reported on two research projects, the first conducted in the early 1990s and the second, a project currently in progress. In essence, the article was an attempt to compare the theology of African Independent Churches in the two respective periods by making use of a grounded theory approach to their worship services. Significant similarities and differences were identified and reported on.